A model of determinants for continuous usage of business intelligence in Malaysian manufacturing organizations using theoretical - Ernie Mazuin Mohd Yusof; Mohd Shahizan Othman; Ahmad Rizal Mohd Yusof; Zirawani Baharum (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Business Intelligence (BI) offered many advantages to organizations adopting the system such as improved decision making and boost organization’s performance. The lack of research on the continuous usage of BI in manufacturing motivates the initiative in this study to have an understanding of the determinants that influenced it. The study proposed a model of individual-related determinants that lead to the continuous usage of BI in manufacturing. A model integrating Unified Theory of Acceptance and Use of Technology (UTAUT) and Information System Continuance Model (ISCM) will be developed. The model will portray 20 hypotheses and 11 determinants leading continuance usage of BI. Data will be collected through survey questionnaires instrument and validated using Structural Equation Modelling (SEM). The result is hoping to show significant relationships between the determinants towards the continuous usage of BI in manufacturing. The study can potentially be used to guide manufacturers and practitioners for considerations in implementing BI in the manufacturing industry.